0
$\begingroup$

I am interested in finding a way to go between the RHS and LHS of the following equation $$\frac{p-1}{p}x+\frac{a}{p}x^{1-p}-a^{1/p}=(x-a^{1/p})\left[\frac{p-1}{p}-\frac{1}{p}\left(\sum_{n=1}^{p-1}\left(\frac{a^{1/p}}{x}\right)^n\right)\right]$$ In the book, it is said it is an "easily" derived formula, however, even after I reversed engineeres the RHS (recognizing geometric sum and simplifying as much as possible) I have been unable to find a way from the left to the right side.
I feel like I must be missing something since this manipulation was supposed to be easy but I do not see it. How would I have gone from the LHS to the RHS?

$\endgroup$
0
$\begingroup$

Working on another way round usually is not easy.

Observe that

\begin{array}{rcl} X^2-2X+1 &=& (X-1)(X-1) \\ 2X^3-3X+1 &=& (X-1)(2X^2-X-1) \\ 3X^4-4X+1 &=& (X-1)(3X^3-X^2-X-1) \\ 4X^5-5X+1 &=& (X-1)(4X^4-X^3-X^2-X-1) \\ & \vdots & \\ (p-1)X^{p}-pX^{p-1}+1 &=& (X-1)[(p-1)X^{p-1}-X^{p-2}-\ldots-X-1] \\ X &=& \dfrac{x}{a^{1/p}} \\ \dfrac{p-1}{p}x+\dfrac{a}{p}x^{1-p}-a^{1/p} &=& \dfrac{(p-1)X^{p}-pX^{p-1}+1}{p}\cdot \dfrac{a^{1/p}}{X^{p-1}} \\ &=& a^{1/p}(X-1) \left[ \dfrac{p-1}{p}-\dfrac{1}{p} \left( 1+\dfrac{1}{X}+\ldots+\dfrac{1}{X^{p-1}} \right) \right] \end{array}

The result follows.

Further point to be noticed: \begin{align*} nx^{n+1}-(n+1)x^{n}+1 &= (x-1)(nx^{n}-x^{n-1}-\ldots-x-1) \\ &= (x-1)^2[nx^{n-2}+(n-1)x^{n-3}+\ldots+2x+1] \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.